In-situ synthesis nano TiB2 reinforced aluminum alloy-based composite powder and preparation method thereof
By presintering the fluorine salt mixed powder and the two-step melting casting method combined with mechanical stirring and electromagnetic stirring technology, the problem of easy agglomeration and difficult to control side reactions in aluminum-based composite materials is solved, and the high-quality preparation and mechanical properties of nano-TiB2 enhanced aluminum alloy-based composite powder are achieved.
Patent Information
- Application Number
- CN202411972790.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, during the preparation process of aluminum-based composites, there are problems such as TiB2 particles being easily agglomerated, difficult to control side reactions, and difficult to remove residual salts, which affects the mechanical properties of the material.
Presintering is used to mix fluorine salt powder to promote the pre-reaction of Ti and B elements and reduce the occurrence of side reactions. Then, a nano-TiB2-reinforced aluminum alloy-based composite material was prepared by a two-step melt casting method, combining mechanical stirring and electromagnetic stirring technology to ensure the uniform distribution of TiB2 particles and the preparation of high-quality composite powder.
It effectively avoids the agglomeration and side reaction of TiB2 particles, improves the mechanical properties and purity of the composite material, and ensures the uniform distribution of TiB2 particles and the high-quality composite powder preparation.
Smart Images

Figure CN119772184A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal-based composite materials, and in particular relates to an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder and a preparation method thereof. Background Art
[0002] Aluminum matrix composites (AMCs) have shown broad application potential in the fields of aviation, aerospace, and automotive industries due to their high specific strength, high specific modulus, good wear resistance, and electrical and thermal conductivity. Particles represented by titanium diboride (TiB2) have low density (4.53 g / cm 3 )、Low thermal expansion coefficient (4.6×10 -6 / ℃), high hardness (2800 HV) and other excellent mechanical properties. Using it as a reinforcement phase material will hopefully further improve the comprehensive mechanical properties of AMCs. However, the wettability between the aluminum matrix and TiB2 particles is poor, and the intrinsic interface bonding is weak, making it difficult to effectively transfer loads. Existing studies have shown that the in-situ self-generation method can be used to prepare ceramic particle-reinforced metal matrix composites, which can reasonably select the reaction components and conditions to control the type, size, quantity and distribution of the reinforcement phase; and can avoid the problem of poor compatibility between the added ceramic particles and the matrix, and improve the bonding between the reinforcement phase and the matrix. Therefore, most of the current studies use the in-situ self-generation method to prepare TiB2-reinforced aluminum-based composites, among which the mixed salt method is a commonly used process for preparing TiB2 particle-reinforced aluminum-based composites by in-situ self-generation. The method comprises the following steps: mixing potassium fluorotitanate (K2TiF6) and potassium fluoroborate (KBF4) containing reinforcing elements Ti and B according to an atomic ratio, and adding the mixture to a molten aluminum melt. The mixed salt reacts chemically under high temperature to generate TiB2 reinforcing body particles. After the reaction is completed, the KAlF4 and K3AlF6 scum are filtered out, and the molten composite material is cast to obtain a TiB2 reinforced Al-based composite material.
[0003] Studies have shown that since the in-situ self-generated TiB2 particles are micro-nano scale and have a large specific surface energy, they are prone to obvious agglomeration in the aluminum melt. This uneven particle distribution will greatly weaken the strengthening effect of the particles on the composite material; on the other hand, the preparation of aluminum-based composites by the in-situ self-generated method is carried out at a relatively high temperature. During the preparation, Ti and B will inevitably react chemically with the aluminum alloy matrix to generate AlB2 and hard-brittle phase TiAl3, forming brittle products at the interface, which reduces the strength of the prepared material; at the same time, in the process of preparing TiB2-reinforced aluminum-based composites by the mixed salt method, KAlF4 and K3AlF6 slags are difficult to remove, resulting in residual salt inclusions, which seriously affect the mechanical properties of the composite material.
[0004] In view of the above-mentioned problems such as easy agglomeration of micro-nano TiB2, difficulty in controlling side reactions during the casting process, and difficulty in removing the slag KAlF4 and K3AlF6, the present invention rationally designs the preparation process of TiB2 reinforced aluminum alloy-based composite materials and proposes a new preparation method of aluminum-based composite materials to achieve the preparation of high-quality TiB2 reinforced aluminum alloy-based composite powders. Summary of the invention
[0005] The purpose of the present invention is to provide an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder and a preparation method thereof, so as to solve the technical problem that the side reactions in the melting and casting process in the existing preparation method are difficult to control.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder, comprising the following steps: Weigh K2TiF6, KBF4 and aluminum ingot as raw materials; The fluoride salt mixed powder is prepared by using K2TiF6 and KBF4, and then the fluoride salt mixed powder is pre-sintered; Then, the fluoride salt mixed powder and aluminum ingot are prepared by melt casting to obtain an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot; The in-situ nano-TiB2 reinforced pure aluminum-based composite ingot is melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Ti, Al-Si, Al-Cr intermediate alloy ingots and pure Zn are added in sequence to obtain an in-situ nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot; The ingot of self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite material is subjected to gas atomization powder making to obtain in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder.
[0007] Furthermore, in terms of mass percentage, the content of the aluminum ingot is 85-99 wt.%; and the mass ratio of K2TiF6 to KBF4 is 0.944:1.
[0008] Furthermore, the fluoride salt mixed powder is obtained by ball milling K2TiF6 and KBF4; the rotation speed of the ball milling is 200-650 r / min, the time is 2-8 h, the ball milling aid used is anhydrous ethanol, and the ball-to-material ratio is (4-10):1; the amount of anhydrous ethanol added is 0.5-2 wt.% of the total mass of the fluoride salt mixed powder; The pre-sintering temperature is 400-600°C and the time is 1-6 hours.
[0009] Furthermore, the specific steps of preparing the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite material ingot by melt-casting the fluoride salt mixed powder and the aluminum ingot are: The aluminum block is melted to obtain molten aluminum liquid; the fluoride salt mixed powder is added into the molten aluminum liquid and stirred to obtain a melt after reaction, and after cooling, an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite material ingot is obtained.
[0010] Further, the melting temperature is 750-900°C; The stirring is firstly mechanical stirring and then electromagnetic stirring and mechanical stirring are performed synchronously; The process parameters of the mechanical stirring are: a rotation speed of 50-200 r / min, stirring for 3-10 min and then stirring in the reverse direction after a 3-10 min pause; the direction of the electromagnetic stirring is alternating between forward and reverse, stirring for 30-200 s and then pausing for 10-30 s before changing the stirring direction, the stirring current is 60-150 A, the stirring frequency is 5-16 Hz, and the insulation time is 15-120 min.
[0011] Furthermore, the specific steps of melting the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot to prepare the in-situ self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot are: The in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot is melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Ti, Al-Si, Al-Cr intermediate alloy ingots and pure Zn are added in sequence to obtain a composite material with 6061 aluminum alloy as the matrix; After further melting the composite material based on 6061 aluminum alloy, a self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot is obtained.
[0012] Furthermore, the melting temperature of the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite material ingot is 750-900°C; In terms of mass percentage, the composite material based on 6061 aluminum alloy contains 0.40-0.8 wt.% of silicon, 0.7 wt.% of iron, 0.15-0.4 wt.% of copper, less than 0.15 wt.% of manganese, 0.8-1.2 wt.% of magnesium, 0.04-0.35% wt.% of chromium, 0.25 wt.% of zinc, and 0.15 wt.% of titanium. During the melting process, mechanical stirring is performed first and then electromagnetic stirring; the process parameters of the mechanical stirring are: a rotation speed of 50-200 r / min, stirring for 3-10 min and then stirring in the opposite direction after 3-10 min of rest; the direction of the electromagnetic stirring is alternating between forward and reverse, stirring for 30-200 s and then pausing for 10-30 s before changing the stirring direction, the stirring current is 60-150 A, the stirring frequency is 5-16 Hz, and the insulation time is 15-120 min.
[0013] Furthermore, the gas atomization powder making method is plasma rotating electrode atomization powder making, vacuum induction melting inert gas atomization powder making or crucible-free electrode induction melting gas atomization powder making.
[0014] The invention also discloses in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder prepared by the preparation method.
[0015] Furthermore, the content of TiB2 generated by in-situ reaction in the in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder is 1-15 wt.%.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder. Firstly, a fluorine salt mixed powder prepared by K2TiF6 and KBF4 is pre-sintered to promote full contact and pre-reaction between Ti and B elements, reduce the probability of generating AlB2 and TiAl3 hard and brittle phases through chemical reaction between Ti and B elements and aluminum matrix during the melting and casting process, and promote the generation of target product TiB2 particles. The subsequent two-step melting and casting method, i.e., firstly, a nano-TiB2 particle reinforced pure aluminum-based composite material billet is prepared by utilizing the in-situ reaction during the melting and casting process, and then a TiB2 reinforced 6061 aluminum alloy-based composite material billet is formed by using the billet as a raw material by adding a certain proportion of intermediate alloy ratio to prepare the aluminum alloy composite powder containing nano-TiB2 particles. The preparation process route can fully promote the generation of nano-TiB2 particles in the composite material, avoid the reaction of alloy elements with aluminum matrix and K2TiF6 and KBF4 to generate byproducts such as TiAl3 and AlB2, reduce the consumption of added alloy elements, and ensure that the chemical composition in the final composite powder is close to the designed ratio.
[0017] Furthermore, the technical route of first performing mechanical stirring and then simultaneously performing electromagnetic stirring and mechanical stirring plays a crucial role in the full reaction and uniform distribution of K2TiF6 and KBF4 raw materials in the aluminum melt, as well as the uniform distribution and separate dispersion of the nanoscale TiB2 particles generated by the reaction in the melt, while at the same time improving the removal rate of the reaction by-products KAlF4 and K3AlF6 salt slag; the use of gas atomization powder making technologies such as plasma rotating electrode atomization powder making (PREP), vacuum induction melting inert gas atomization powder making (VIGA) or crucible-free electrode induction melting gas atomization powder making (EIGA) can ensure the purity, sphericity and yield of the prepared composite powder.
[0018] The present invention also discloses an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder prepared by the above-mentioned preparation method. The composite powder has high sphericity and low impurity content. TiB2 is evenly distributed at the nanoscale and the content is controllable, which overcomes the problems of uneven distribution, incomplete slag removal and difficult to control side reactions in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Metallographic photographs of the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot and the in-situ self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot prepared in Example 1 of the present invention and the TiB2 particle reinforced pure aluminum-based composite ingot obtained in Comparative Example 1; Wherein: a-Example 1 in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot; b-Example 2 prepared in-situ self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot; c-Comparative Example 1 prepared Al-5TiB2 composite ingot microstructure photograph; Figure 2 The scanning photo and energy spectrum scanning result of the in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder prepared in Example 1 of the present invention; Wherein: a-microscopic morphology photo of TiB2 reinforced aluminum alloy composite powder prepared by the present invention; b-cross-sectional microscopic morphology photo of composite powder; c-cross-sectional microstructure photo of composite powder; d and e-are EDS surface scanning results of Ti and B elements of cross-sectional microstructure of composite powder in Figure c, respectively; Figure 3 This is the X-ray diffraction pattern of the 6061Al-TiB2 composite powder prepared in Example 1. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0025] The present invention provides a method for preparing in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder, comprising the following steps: Step 1, weigh the following components according to mass percentage: aluminum ingot 85-99 wt.%, K2TiF6 and KBF mass ratio of 0.944 (Ti, B atomic ratio of 1:2.02), K2TiF6 and KBF mass ratio of 0.944 (Ti, B atomic ratio of 1:2.02), the sum of the mass fractions of the above components is 100%; the purity of the aluminum ingot, K2TiF6 and KBF4 is ≥99.9%; Step 2, placing K2TiF6 and KBF4 in a ball mill, and performing ball milling treatment by roller ball milling to obtain a fluoride salt mixed powder, and adding 0.5-2 wt.% anhydrous ethanol as a ball milling aid during the ball milling treatment; The ball milling mixing time is 2-8 h, the ball milling speed is 200-650 r / min, the ball-to-material ratio is 4-10:1, and the grinding balls are zirconium oxide (the ratio of large and small balls is 2-4:1); Step 3, placing the mixed fluoride salt powder in a vacuum sintering furnace for pre-sintering; the pre-sintering temperature is 400-600 ° C, and the sintering time is 1-6 h; Step 4: Place the aluminum ingot in a crucible and melt it in a vacuum environment or an inert gas atmosphere at a melting temperature of 750-900 °C. Add the solvent cryolite (sodium fluoroaluminate Na3AlF6). After the aluminum ingot is melted, wrap the mixed fluoride salt with aluminum foil and add it to the molten aluminum liquid in batches. First, start mechanical stirring for 10-90 min, then apply electromagnetic stirring synchronously. The directions of mechanical stirring and electromagnetic stirring are alternating. The process parameters of mechanical stirring are: speed 50-200 r / min, stirring for 3-10 min and then stirring in the opposite direction after 3-10 min interval. The direction of electromagnetic stirring is alternating, stirring for 30-200 s and then pausing for 10-30 s before changing the stirring direction. The stirring current is 60-150 A and the stirring frequency is 5-16 Hz. Refining agent magnesium chloride is added during the process, and the scum on the surface of the melt is removed several times, and then the temperature is kept for 15-120 min to obtain an in-situ nano-TiB2 reinforced pure aluminum-based composite ingot (Al-TiB2 composite material); The in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot is melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Si, Al-Cr alloy ingots and pure Zn particles are added according to the proportion of 6061 aluminum alloy to obtain a composite material based on 6061 aluminum alloy; the composite material contains 0.40-0.8 wt.% of silicon, 0.7 wt.% of iron, 0.15-0.4 wt.% of copper, 0.15 wt.% of manganese, 0.8-1.2 wt.% of magnesium, 0.04-0.35% wt.% of chromium, 0.25 wt.% of zinc, and 0.15 wt.% of titanium; the composite material based on 6061 aluminum alloy is further melted, kept warm for 15-60 min, and then cast to obtain an in-situ self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot; electromagnetic stirring is maintained during the process, and the electromagnetic stirring process alternates between positive and negative directions, and the stirring is performed for 30-200 After 10-30 s, change the stirring direction, the stirring current is 60-150 A, and the stirring frequency is 5-16 Hz; Electromagnetic stirring technology is used in the smelting process. This technology has the characteristics of non-contact and artificially controllable electromagnetic force. It can convert electromagnetic energy into kinetic energy of molten aluminum without contacting molten aluminum, reducing the introduction of impurities; and the direction and rate of aluminum liquid flow can be artificially controlled, which can effectively promote the uniform dispersion of nano-enhanced phases. High-quality composite ingots can be obtained by adjusting parameters; Step 6: Use the prepared self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite material ingot as the anode material, and use gas atomization technology to spray powder to obtain in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder.
[0026] The above-mentioned gas atomization technology can be carried out by plasma rotating electrode (PREP) or vacuum induction melting inert gas atomization (VIGA) or crucible-free electrode induction melting gas atomization (EIGA), which can improve the yield of composite powder and have higher purity and sphericity.
[0027] The present invention has the following technical advantages: the present invention promotes the pre-reaction between Ti and B by pre-sintering the mixed salt, thereby reducing the occurrence of side reactions during the casting process, that is, improving the purity of the reinforcing phase in the composite powder; and combines the resistance smelting technology with the electromagnetic stirring process to promote the reaction between Ti and B to generate TiB2, avoid the agglomeration of in-situ self-generated nano-TiB2 reinforcing phase particles, and improve the discharge of salt slag, effectively ensuring the purity of the composite material and the uniform dispersion of the reinforcing phase in the aluminum matrix, so as to reduce the stress concentration tendency caused by salt slag inclusions or TiB2 agglomeration; adopts plasma rotating electrode (PREP) / vacuum induction melting inert gas atomization (VIGA) / crucible-free electrode induction melting gas atomization (EIGA) and other gas atomization technologies for powder spraying, thereby improving the purity, sphericity and yield of the composite powder.
[0028] In summary, the in-situ self-generated TiB2 reinforced 6061 aluminum-based composite powder finally obtained by the preparation method of the present invention has fewer side reaction products, a low salt slag inclusion rate, TiB2 is uniformly dispersed in the matrix in the form of nano-scale particles, and the composite powder has high purity, sphericity and yield.
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0031] Example 1 A method for preparing in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder comprises the following steps: Step 1. Weigh the following components according to mass percentage: 3 kg pure aluminum ingot, 490.3 g K2TiF6 and 19.3 g KBF45; Step 2, placing K2TiF6 and KBF4 raw material powders in a ball mill, and using a roller ball mill to perform ball milling to obtain a fluoride salt mixed powder, during which 2 wt.% anhydrous ethanol is added as a ball milling aid; the ball milling mixing time is 4 h, the ball milling speed is 650 r / min, the ball-to-material ratio is 5:1, and the grinding balls are zirconium oxide (the ratio of large and small balls is 4:1); Step 3, placing the mixed fluoride salt powder in a vacuum sintering furnace for pre-sintering; the pre-sintering temperature is 500 ° C, and the sintering time is 4 h; Step 4, placing the aluminum ingot in a crucible, melting it in a vacuum environment or an inert gas atmosphere, the melting temperature is 850 ° C, adding 20.2 g of the auxiliary solvent cryolite (sodium fluoroaluminate Na3AlF6), and after the aluminum ingot is melted, wrapping it with aluminum foil, adding the mixed fluoride salt to the molten aluminum liquid in batches, adding it to the molten aluminum liquid in batches, first turning on the mechanical stirring for 30 minutes, and then applying electromagnetic stirring synchronously, the directions of the mechanical stirring and electromagnetic stirring process are alternating in positive and negative directions, and the process parameters of mechanical stirring are: speed 120 r / min, stirring in the opposite direction after 5 minutes of rest, stirring in the reverse direction after 5 minutes, stirring for 50 seconds and then pausing for 10 seconds before changing the stirring direction, the stirring current is 120 A, the stirring frequency is 10 Hz, adding 20.2 g of the refining agent magnesium chloride during the process, and removing the scum on the surface of the melt several times, and then keeping warm for 60 minutes to obtain an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot (Al-TiB2 composite material); The in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot was melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Si, Al-Cr alloy ingots and pure Zn particles 40.3 g, 54.1 g, 19.4 g, 64.9 g, 54.8 g, 40.6 g, and 6.2 g were added according to the proportion of 6061 aluminum alloy to obtain a composite material with 6061 aluminum alloy as the matrix; containing 0.7 wt.% of silicon, 0.7 wt.% of iron, 0.4 wt.% of copper, 0.1 wt.% of manganese, 1.2 wt.% of magnesium, 0.2 wt.% of chromium, 0.25 wt.% of zinc, and 0.15 wt.% of titanium; after the composite material with 6061 aluminum alloy as the matrix was further melted, the directions of mechanical stirring and electromagnetic stirring were alternated in positive and negative directions, the mechanical stirring speed was 120 r / min, stirring was performed in the opposite direction after 5 min of rest, and electromagnetic stirring was 50 After 20 s of rest, the stirring direction was changed, the stirring current was 130 A, the stirring frequency was 10 Hz, and after keeping warm for 30 min, casting was performed to obtain an in-situ nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot (TiB2 mass fraction was 5wt.%). Step 6: The prepared self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot is used as the anode material, and the powder is sprayed by gas atomization technology to obtain in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder; the process parameters of the gas atomization technology are: evacuate to a vacuum degree of less than 5×10 -2 Pa, and then fill it with argon gas with a purity of 99.9% to fill the atomization chamber with argon gas; start the rotary feeder until the speed reaches 15000 r / min, start the particle gun power supply, make the current intensity reach 1500A, generate a high-temperature plasma arc, melt the rod, the material feed rate is 0.8 mm / s, and plasma rotary electrode atomization powder making is carried out.
[0032] Example 2 A method for preparing in-situ self-generated nano-1 wt.% TiB2 reinforced aluminum alloy-based composite powder comprises the following steps: Step 1. Weigh the following components according to mass percentage: 3 kg pure aluminum ingot, 3.3 g K2TiF610 and 9.5 g KBF410; Step 2, placing K2TiF6 and KBF4 raw material powders in a ball mill, and using a roller ball mill to perform ball milling to obtain a fluoride salt mixed powder, during which 2 wt.% anhydrous ethanol is added as a ball milling aid; the ball milling mixing time is 4 h, the ball milling speed is 650 r / min, the ball-to-material ratio is 5:1, and the grinding balls are zirconium oxide (the ratio of large and small balls is 4:1); Step 3, placing the mixed fluoride salt powder in a vacuum sintering furnace for pre-sintering; the pre-sintering temperature is 500 ° C, and the sintering time is 2 h; Step 4, placing the aluminum ingot in a crucible, melting it in a vacuum environment or an inert gas atmosphere, the melting temperature is 850 ° C, adding 20.2 g of the auxiliary solvent cryolite (sodium fluoroaluminate Na3AlF6), and after the aluminum ingot is melted, wrapping it with aluminum foil, adding the mixed fluoride salt to the molten aluminum liquid in batches, adding it to the molten aluminum liquid in batches, first turning on the mechanical stirring for 30 minutes, and then applying electromagnetic stirring synchronously, the directions of the mechanical stirring and electromagnetic stirring process are alternating in positive and negative directions, and the process parameters of mechanical stirring are: speed 120 r / min, stirring in the opposite direction after 5 minutes of rest, stirring in the reverse direction after 5 minutes, stirring for 50 seconds and then pausing for 10 seconds before changing the stirring direction, the stirring current is 120 A, the stirring frequency is 10 Hz, adding 20.2 g of the refining agent magnesium chloride during the process, and removing the scum on the surface of the melt several times, and then keeping warm for 30 minutes to obtain an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot (Al-TiB2 composite material); The in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot was melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Si, Al-Cr alloy ingots and pure Zn particles 40.3 g, 54.1 g, 19.4 g, 64.9 g, 54.8 g, 40.6 g, and 6.2 g were added according to the proportion of 6061 aluminum alloy to obtain a composite material with 6061 aluminum alloy as the matrix; containing 0.7 wt.% silicon, 0.7 wt.% iron, 0.4 wt.% copper, 0.1 wt.% manganese, 1.2 wt.% magnesium, 0.2 wt.% chromium, 0.25 wt.% zinc, and 0.15 wt.% titanium; after the composite material with 6061 aluminum alloy as the matrix was further melted, the mechanical stirring and electromagnetic stirring processes were alternated in forward and reverse directions, the mechanical stirring speed was 120 r / min, stirring was performed in the opposite direction after 5 min of rest, and the electromagnetic stirring was 50 After 20 s of rest, the stirring direction was changed, the stirring current was 130 A, the stirring frequency was 10 Hz, and after keeping warm for 30 min, casting was performed to obtain in-situ nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot (TiB2 mass fraction was 1 wt.%). Step 6: The prepared self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot is used as the anode material, and the powder is sprayed by gas atomization technology to obtain in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder; the process parameters of the gas atomization technology are: evacuate to a vacuum degree of less than 5×10 -2Pa, and then fill it with argon gas with a purity of 99.9% to fill the atomization chamber with argon gas; start the rotary feeder until the speed reaches 15000 r / min, start the particle gun power supply, make the current intensity reach 1500A, generate a high-temperature plasma arc, melt the rod, the material feed rate is 0.8 mm / s, and plasma rotary electrode atomization powder making is carried out.
[0033] Example 3 A method for preparing an in-situ self-generated nano-15 wt.% TiB2-reinforced aluminum alloy-based composite powder comprises the following steps: Step 1. Weigh the following components according to mass percentage: 3 kg pure aluminum ingot, 1488.7 g K2TiF6 and 1576.9 g KBF4; Step 2, placing K2TiF6 and KBF4 raw material powders in a ball mill, and using a roller ball mill to perform ball milling to obtain a fluoride salt mixed powder, during which 2 wt.% anhydrous ethanol is added as a ball milling aid; the ball milling mixing time is 4 h, the ball milling speed is 650 r / min, the ball-to-material ratio is 5:1, and the grinding balls are zirconium oxide (the ratio of large and small balls is 4:1); Step 3, placing the mixed fluoride salt powder in a vacuum sintering furnace for pre-sintering; the pre-sintering temperature is 500 ° C, and the sintering time is 6 h; Step 4, placing the aluminum ingot in a crucible, melting it in a vacuum environment or an inert gas atmosphere, the melting temperature is 850 ° C, adding 20.2 g of the solvent cryolite (sodium fluoroaluminate Na3AlF6), and after the aluminum ingot is melted, wrapping it with aluminum foil, adding the mixed fluoride salt to the molten aluminum liquid in batches, adding it to the molten aluminum liquid in batches, first turning on the mechanical stirring for 30 minutes, and then applying electromagnetic stirring synchronously, the directions of the mechanical stirring and electromagnetic stirring process are alternating in positive and negative directions, and the process parameters of mechanical stirring are: speed 120 r / min, stirring in the opposite direction after 5 minutes of rest, stirring in the reverse direction after 5 minutes of stirring, the electromagnetic stirring process direction is alternating in positive and negative directions, stirring for 50 seconds and then pausing for 10 seconds before changing the stirring direction, the stirring current is 120 A, the stirring frequency is 10 Hz, 20.2 g of the refining agent magnesium chloride is added during the process, and the scum on the surface of the melt is removed several times, and then the heat is kept for 120 minutes to obtain an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot (Al-TiB2 composite material); The in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot was melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Si, Al-Cr alloy ingots and pure Zn particles 40.3 g, 54.1 g, 19.4 g, 64.9 g, 54.8 g, 40.6 g, and 6.2 g were added according to the proportion of 6061 aluminum alloy to obtain a composite material with 6061 aluminum alloy as the matrix; containing 0.7 wt.% silicon, 0.7 wt.% iron, 0.4 wt.% copper, 0.1 wt.% manganese, 1.2 wt.% magnesium, 0.2 wt.% chromium, 0.25 wt.% zinc, and 0.15 wt.% titanium; after the composite material with 6061 aluminum alloy as the matrix was further melted, the mechanical stirring and electromagnetic stirring processes were alternated in forward and reverse directions, the mechanical stirring speed was 120 r / min, stirring was performed in the opposite direction after 5 min of rest, and the electromagnetic stirring was 50 After 20 s of rest, the stirring direction was changed, the stirring current was 130 A, the stirring frequency was 10 Hz, and after keeping warm for 30 min, casting was performed to obtain in-situ nano-TiB2 reinforced 6061 aluminum alloy matrix composite ingot (TiB2 mass fraction was 15 wt.%). Step 6: The prepared self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot is used as the anode material, and the powder is sprayed by gas atomization technology to obtain in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder; the process parameters of the gas atomization technology are: evacuate to a vacuum degree of less than 5×10 -2 Pa, and then fill it with argon gas with a purity of 99.9% to fill the atomization chamber with argon gas; start the rotary feeder until the speed reaches 15000 r / min, start the particle gun power supply, make the current intensity reach 1500A, generate a high-temperature plasma arc, melt the rod, the material feed rate is 0.8 mm / s, and plasma rotary electrode atomization powder making is carried out.
[0034] Comparative Example 1 The Al-5TiB2 comparative composite material ingot was prepared by a process route different from that in Example 1, specifically according to the following steps: Step 1, weigh the following components according to mass percentage: 3 kg pure aluminum ingot, 490.3 g K2TiF6 (potassium fluorotitanate) and 519.3 g KBF4 (potassium fluoroborate), that is, the mass fraction of TiB2 generated by in-situ reaction is 5 wt.%, the aluminum matrix is 95 wt.%, and the sum of the mass fractions of the above components is 100%; Step 2, placing K2TiF6 and KBF4 raw material powders in a ball mill, mixing them by roller milling to obtain a mixed fluoride salt, adding 0.5-2 wt.% anhydrous ethanol as a ball milling aid during the ball milling process; the ball milling mixing time during the roller milling process is 4h, the ball milling speed is 600 r / min, the ball-to-material ratio is 5:1, and the grinding balls are zirconium oxide (the ratio of large and small balls is 4:1); Step 3, wrap the mixed fluoride salt with tin foil and place it in a vacuum drying oven for drying at 120 °C for 4 h; Step 4: Place the pure aluminum block weighed in proportion in a crucible, add 20.2 g of cryolite (sodium fluoroaluminate Na3AlF6) as a flux, melt it in an argon atmosphere, and the melting temperature is 850 ° C. After the aluminum block is melted, wrap the mixed fluoride salt with aluminum foil and add it to the molten aluminum liquid in batches. During the process, add 20.2 g of refining agent magnesium chloride, start mechanical stirring, and the process parameters of mechanical stirring are: speed 120 r / min, stir for 5 min and then stir in the opposite direction after 5 min of rest, and remove the scum on the surface of the melt several times, then keep it warm for 60 min, and then cast it into a Φ52×260 mm graphite mold for cooling and solidification. Repeat the above process twice to remove the by-products generated by the reaction in the melt, and finally obtain an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot.
[0035] The following are the test results of the microstructure morphology and phase composition of the in-situ self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot and composite powder prepared by the present invention, as follows: Figure 1 The metallographic photographs of the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot and the in-situ self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot prepared in Example 1 of the present invention and the TiB2 particle reinforced pure aluminum-based composite ingot obtained in Comparative Example 1 show that in the composite ingot obtained in Comparative Example 1, there are more reaction products KAlF4 and K3AlF6 salt slag that have not been completely removed, but no obvious inclusions are observed in the microstructure of the composite ingot obtained by the preparation technology of the present application, indicating that the technical route of the present application can fully promote the generation of nano-TiB2 particles in the composite material while avoiding the reaction of alloy elements with the aluminum matrix and K2TiF6 and KBF4 to generate by-products such as TiAl3 and AlB2; the technical route of first performing mechanical stirring and then simultaneously performing electromagnetic stirring and mechanical stirring plays a beneficial role in the full reaction and uniform distribution of the K2TiF6 and KBF4 raw materials in the aluminum melt and the uniform distribution and separate dispersion of the nano-scale TiB2 particles generated by the reaction in the melt, thereby improving the removal rate of the reaction by-products KAlF4 and K3AlF6 salt slag.
[0036] Figure 2The scanning photo and the spectrum scanning result of the in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder prepared in Example 1 of the present invention show that the composite powder has a high sphericity and no satellite powder. The powder yield rate with an average particle size range of 50 μm-106 μm is 70%. Figure 2 (b) No obvious hollow powder was observed in the cross section of the composite powder. Figure 2 (c) It can be seen that a large number of nanoparticles are dispersed in the matrix. The element surface analysis results show that the nanoparticles are mainly composed of Ti and B, which indicates that the vacuum pre-sintering of the mixed salt in the present invention effectively promotes the reaction between Ti and B and inhibits the production of by-products TiAl3 and AlB2. At the same time, the nano-scale TiB2 particles are distributed in a quasi-continuous network along the grain boundaries in the aluminum alloy matrix without obvious agglomeration.
[0037] Figure 3 This is the X-ray diffraction pattern of the 6061Al-TiB2 composite powder prepared in Example 1 of the present invention. It can be seen that characteristic peaks of Al, TiB2 and Mg2Si appear in the spectrum, and no other impurity peaks are observed, indicating that the 6061Al-5TiB2 aluminum-based composite powder prepared by the present invention has a high purity.
[0038] In summary, the present invention effectively promotes the reaction between Ti and B and inhibits the production of by-products TiAl3 and AlB2 by vacuum pre-sintering the mixed fluoride salt; a two-step melting and casting method is used, i.e., firstly, a nano-TiB2 particle-reinforced pure aluminum-based composite material ingot is prepared by utilizing the in-situ reaction during the melting and casting process, and then a TiB2-reinforced 6061 aluminum alloy-based composite material ingot is formed by using this as a raw material and adding a certain proportion of an intermediate alloy ratio to prepare an aluminum alloy composite powder containing nano-TiB2 particles. The preparation process route fully promotes the production of nano-TiB2 particles in the composite material; inhibits the reaction of alloy elements with the aluminum matrix and fluoride salts. The production of reaction by-products reduces the consumption of alloy elements; the technical route of first mechanical stirring and then synchronous electromagnetic stirring plays a vital role in the full reaction and uniform distribution of the fluorine salt raw material in the aluminum melt and the uniform distribution and separate dispersion of the nano-scale TiB2 particles generated by the reaction in the melt, and at the same time improves the removal rate of the reaction by-products KAlF4 and K3AlF6 salt slag; the 6061Al-TiB2 aluminum-based composite powder prepared by plasma rotating electrode atomization powder preparation has a high sphericity, no satellite powder and hollow powder, and the microstructure and phase characterization results show that the prepared composite powder has a low impurity content. Therefore, the present invention prepares high-quality 6061Al-TiB2 composite powder with controllable and fine reinforcing phase content, high sphericity and low impurity content, and the formed in-situ self-generated aluminum alloy composite powder preparation technology can be expanded to the preparation and development of various aluminum alloy-based composite powders containing nano-reinforcement phases.
[0039] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder, characterized in that: The following steps are involved: Weigh K2TiF6, KBF4 and aluminum ingot as raw materials; The fluoride salt mixed powder is prepared by using K2TiF6 and KBF4, and then the fluoride salt mixed powder is pre-sintered; Then, the fluoride salt mixed powder and aluminum ingot are prepared by melt casting to obtain an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot; The in-situ nano-TiB2 reinforced pure aluminum-based composite ingot is melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Ti, Al-Si, Al-Cr intermediate alloy ingots and pure Zn are added in sequence to obtain an in-situ nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot; The ingot of self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite material is subjected to gas atomization powder making to obtain in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder.
2. The method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 1, characterized in that: In the raw materials, the content of aluminum ingot is 85-99 wt.% by mass; the mass ratio of K2TiF6 to KBF4 is 0.944:
1.
3. The method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 1, characterized in that: The fluoride salt mixed powder is obtained by ball milling K2TiF6 and KBF4; the rotation speed of the ball milling is 200-650 r / min, the time is 2-8 h, the ball milling aid used is anhydrous ethanol, and the ball-to-material ratio is (4-10):1; the addition amount of the anhydrous ethanol is 0.5-2 wt.% of the total mass of the fluoride salt mixed powder; The pre-sintering temperature is 400-600°C and the time is 1-6 hours.
4. The method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 1, characterized in that: The specific steps of preparing the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite material ingot by melt-casting the fluoride salt mixed powder and the aluminum ingot are as follows: The aluminum block is melted to obtain molten aluminum liquid; the fluoride salt mixed powder is added into the molten aluminum liquid and stirred to obtain a melt after reaction, and after cooling, an in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite material ingot is obtained.
5. The method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 4, characterized in that: The melting temperature is 750-900°C; The stirring is performed by first performing mechanical stirring and then performing electromagnetic stirring; The process parameters of the mechanical stirring are: a rotation speed of 50-200 r / min, stirring for 3-10 min and then stirring in the reverse direction after a 3-10 min pause; the direction of the electromagnetic stirring is alternating between forward and reverse, stirring for 30-200 s and then pausing for 10-30 s before changing the stirring direction, the stirring current is 60-150 A, the stirring frequency is 5-16 Hz, and the insulation time is 15-120 min.
6. The method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 1, characterized in that: The specific steps of melting the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot to prepare the in-situ self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot are as follows: The in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite ingot is melted, and Al-Mn, Al-Fe, Al-Cu, Al-Mg, Al-Ti, Al-Si, Al-Cr intermediate alloy ingots and pure Zn are added in sequence to obtain a composite material with 6061 aluminum alloy as the matrix; After further melting the composite material based on 6061 aluminum alloy, a self-generated nano-TiB2 reinforced 6061 aluminum alloy-based composite ingot is obtained.
7. The method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 6, characterized in that: The melting temperature of the in-situ self-generated nano-TiB2 reinforced pure aluminum-based composite material ingot is 750-900°C; In terms of mass percentage, the composite material based on 6061 aluminum alloy contains 0.40-0.8 wt.% of silicon, 0.7 wt.% of iron, 0.15-0.4 wt.% of copper, less than 0.15 wt.% of manganese, 0.8-1.2 wt.% of magnesium, 0.04-0.35% wt.% of chromium, 0.25 wt.% of zinc, and 0.15 wt.% of titanium. During the melting process, mechanical stirring is performed first and then electromagnetic stirring and mechanical stirring are performed synchronously; the process parameters of the mechanical stirring are: a rotation speed of 50-200 r / min, stirring for 3-10 min and then stirring in the opposite direction after 3-10 min of rest; the direction of the electromagnetic stirring is alternated between forward and reverse, stirring for 30-200 s and then pausing for 10-30 s before changing the stirring direction, the stirring current is 60-150 A, the stirring frequency is 5-16 Hz, and the insulation time is 15-120 min.
8. The method for preparing an in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 1, characterized in that: The gas atomization powder making method is plasma rotating electrode atomization powder making, vacuum induction melting inert gas atomization powder making or crucible-free electrode induction melting gas atomization powder making.
9. An in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder, characterized in that: The method is prepared by any one of claims 1 to 8.
10. The in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder according to claim 9, characterized in that: The content of TiB2 generated by in-situ reaction in the in-situ self-generated nano-TiB2 reinforced aluminum alloy-based composite powder is 1-15wt.%.